Independent and combined associations of depressive symptoms and sleep disturbance with chronic pain in community-dwelling older adults. (14th September 2022) - Saito, Takafumi; Chen, Tao; Yatsugi, Harukaze; Chu, Tianshu; Liu, Xin; Kishimoto, Hiro
Abstract : Supplemental Digital Content is Available in the Text. The combination of depressive symptoms and sleep disturbance was positively associated with chronic pain, but there were no additive interactions in community-dwelling older adults. Abstract: Introduction: There is limited evidence regarding whether depressive symptoms and sleep disturbance are independently or synergistically associated with chronic pain. Objectives: We investigated the independent and combined associations of depressive symptoms and sleep disturbance with chronic pain and its severity (and the additive interactions) in community-dwelling older adults. Methods: This cross-sectional study analyzed the data of 1374 individuals who were 65 to 75 year old, not in need of long-term care, and completed questionnaires assessing sociodemographic factors, depressive symptoms, sleep disturbance, and chronic pain. The severity of chronic pain was assessed based on pain intensity, pain distribution, and pain type. The participants' status of depressive symptoms and sleep disturbance were categorized in the following 4 groups: neither condition, depressive symptoms alone, sleep disturbance alone, and both conditions. Results: Among the 1374 participants, 849 (61.8%) had chronic pain. The multivariable-adjusted odds ratios and 95% confidence intervals of the presence of chronic pain in those with depressive symptoms alone, sleep disturbance alone, and both conditions were 1.40 (0.97–2.03), 1.98 (1.41–2.78), and 2.12 (1.39–2.23), respectively, compared with the neither-condition group. Similar associations were observed for severe chronic pain. However, there were no significant additive interactions. In addition, only sleep disturbance was significantly associated with chronic pain, after adjusting for depressive symptoms. Conclusions: Our analyses did not reveal a synergistic effect of depressive symptoms and sleep disturbance on chronic pain and its severity, suggesting that most of the effects of depressive symptoms on chronic pain may be mediated by sleep disturbance.